Probiotic activity of Enterococcus faecalis CECT7121: effects on mucosal immunity and intestinal epithelial cells - Castro, Marisa Silvia (2016)
Aims: To analyse the effect of Enterococcus faecalis CECT7121 on intestinalepithelial cells (IECs) and its effects on the mucosal immune response. Methods and Results: Enterococcus faecalis CECT7121 showed a high adhesioncapacity to completely and heterogeneously differentiated human intestinalepithelial cell line (Caco-2 cells). In addition, the contact of this bacteriumwith Caco-2 cells did not induce inflammatory chemokines (IL-8 and CCL-20). The presence of IgA⁺ and IL-6⁺ cells in the small intestine, as well as theproduction of inflammatory cytokines (TNFa, IL-6 and IL-12) in the gut, wasdetermined after intragastric inoculation of Ent. faecalis CECT7121 in BALB/cmice. The administration of Ent. faecalis CECT7121 increased the number ofIgA⁺ cells in the intestinal lamina propria without modifying the percentage ofIL-6⁺ cells. No differences were observed in the cytokines measured in theintestinal extracts between probiotic-treated and control mice. Conclusions: Enterococcus faecalis CECT7121 stimulates local mucosalimmunity and adheres to IECs without inducing inflammatory signals. Significance and Impact of the Study: Our results indicate that, apart from itsalready reported systemic immune activity, Ent. faecalis CECT7121 has amodulatory effect at a local level.